Identification of effective DNA barcodes for Triticum plants through chloroplast genome-wide analysis. (December 2017) - Awad, Mohamed; Fahmy, Ragab M.; Mosa, Kareem A.; Helmy, Mohamed; El-Feky, Fawzy A.
Graphical abstract: Highlights: We pursued a bioinformatics approach to determine the most useful loci which may be used as DNA barcodes for the Triticum plant species. Ten available chloroplast genomes of 10 Triticum species and sub-species were analyzed. A total of 134 chloroplast genes, gene combinations, intergenic regions and intergenic region combinations were assessed. A novel combination of different intergenic regions has been identified with very high discrimination capacity. These could be utilized as effective DNA barcodes for the Triticum and other Poaceae members. Abstract: The Egyptian flora is rich with a large number of Triticum plants, which are very difficult to discriminate between in the early developmental stages. This study assesses the significance of using two DNA Barcoding loci ( matK and rbcL ) in distinguishing between 18 different Triticum accessions in Egypt. We isolated and sequenced 15 rbcL and six matK fragments, but our analysis of the resultant sequences demonstrated a limited ability of matK and rbcL in distinguishing between Triticum accessions. Therefore, we pursued a bioinformatics approach to determine the most useful loci which may be used as DNA barcodes for the Triticum spp . We obtained the 10 available chloroplast genomes of the 10 Triticum species and sub-species from NCBI, and performed chloroplast genome-wide analysis to find the potential barcode loci. A total of 134 chloroplast genes, gene combinations, intergenic regions and intergenic region combinations were tested using a Tree-based method. We were unable to discriminate between Triticum species by using chloroplast genes, gene combinations and intergenic regions. However, a combination of the intergenic region ( trnfM-trnT ) with either ( trnD-psbM ), ( petN-trnC ), ( matK-rps16 ) or ( rbcL-psaI ) demonstrated a very high discrimination capacity, suggesting their utilization as DNA barcodes for the Triticum plants. Furthermore, our novel DNA barcodes demonstrated high discrimination capacity for other Poaceae members.